DESAIN PEMBELAJARAN KERUCUT MENGGUNAKAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) BERKONTEKS TRADISI MITONI - Asokawati, Indhi; Harun, Lukman; Nursyahidah, Farida (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
Students need to master conic material when studying curved-sided geometric figures. However, cone material is still difficult for students to understand. Therefore, this research aims to create a learning trajectory that can make students understand the concept of cones using the context of the mitoni tradition in class IX SMP. Using the design research method, this method has three stages, namely preliminary design, design experiment (pilot experiment and teaching experiment), and retrospective analysis. This research was designed and developed using the Indonesian Realistic Mathematics Education (PMRI) approach. The research subjects consisted of 32 class IX students at SMP Negeri 39 Semarang, which was carried out from August to September 2023. The results of this research were a learning trajectory that included a series of learning processes with three activities, namely observing videos of the mitoni tradition to find the elements of cones; find the formula for the surface area of a cone; determine the formula for the volume of a cone; and solving contextual problems related to cones. This activity was carried out to increase students' understanding of cone material. The research results show that the context of the mitoni tradition can help students understand the concept of cones. Apart from that, the results of this research present alternative local wisdom that can be used in mathematics, especially in cone materials.